Design of Power Factor Monitoring System Based on Android Application - Fadhillah Hazrina; Inu Yuni Erawati; Galih Mustiko Aji; Devi Taufiq Nurrohman (Andalas Journal of Electrical and Electronic Engineering Technology, 2023)
Electrical energy is an essential resource for human needs. The prolific utilization of electrical devices accounts for high energy consumption patterns. Resistive and inductive loads characterize conventional electrical equipment. In practice, the properties of electrical loads impact energy demand and system efficiency. Thus, power factor correction presents a viable strategy to improve electrical energy efficiency. This research aims to develop an Internet of Things-integrated power factor monitoring system. When connected to Wi-Fi, the system employs a PZEM-004T sensor to monitor current, voltage, power, and power factor measurements from the load in the absence of active monitoring. The ESP32 microcontroller processes the sensor data. Then, control programs running on the microcontroller instruct a relay to engage capacitive banks accordingly. The system displays output metrics on a Liquid Crystal Display and Android application. Experimental results indicate that a single-phase electric motor operates at a baseline power factor of 0.31. However, integration of the factor correction tool detailed herein improves the power factor to 0.98 for the given load.